Implementasi P5 Dalam Meningkatkan Kreativitas dan Gotong Royong Siswa SMPN 6 Kota Serang Melalui Pembuatan Gerabah - Siti Maptuhah; Aulyanissa Tsaqifa Maharshall; Adhela Rahma Apriyanti; Nur Triana Putri; Ilham Kusuma Prabuningrat; Afdal Eki Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia has an important pottery cultural heritage to preserve. This study aims to integrate culture-based education into the Merdeka Curriculum through P5, focusing on pottery making. The objectives of this study are to improve students' creativity, mutual cooperation, and social skills, as well as to strengthen the relationship between schools and communities in preserving local cultural traditions. This study uses a qualitative descriptive method to describe the implementation of P5 activities through pottery making in improving creativity and mutual cooperation at SMP Negeri 6 Kota Serang. Data were obtained through observation, interviews, and documentation from 1119 students and teachers. The results of the study will provide an in-depth picture of the impact of these activities on students at the school. Pottery making activities at SMP Negeri 6 Kota Serang develop students' creativity, motor skills, and mutual cooperation. By drawing designs, shaping, and painting pottery, they learn to think creatively, solve problems, and work together in groups. This activity supports the formation of Pancasila characters, such as togetherness, responsibility, and personal initiative, in accordance with the objectives of the Merdeka curriculum. P5 activities at SMP Negeri 6 Kota Serang have succeeded in achieving the goals of the independent curriculum, creating a Pancasila Student Profile that is creative, cooperative, and has good character. Students develop creativity and collaboration skills through challenging projects. This study emphasizes the importance of an art project-based approach to building the character of Pancasila students in the era of character education.